Analisis Eskalasi pada Proyek Multiyears (Studi Kasus Pembangunan Pengendalian Kerusakan Longsoran Tebing Sungai Lawe Alas Kabupaten Aceh Tenggara) - Muhammad Ridha; Amalia Effendy; Muhammad Irfan (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The purpose of the study is to analyze the value of the price escalation of the work item for the Damage Control (Avalanche) Development Project for the Lawe Alas River Cliff, Southeast Aceh Regency. The result of the escalation calculation based on the contract value in the 13th month is Rp. 53,048.010,455, of the total contract value of Rp. 104,415,0005,000, or an escalated value of 50.80% of the contract price. Escalation calculation method used the formula contained in Presidential Decree no. 16 of 2018 article 37, with quantity data obtained from field measurements and stated in the final addendum terms and contracts. The component index is obtained from the relevant ministerial decree and the price index from the Central Statistics Agency (BPS). The calculation is done by looking at the progress and delays in the schedule. From the calculation, the Escalation Value obtained is Rp. 708,990,794 with a percentage of 1.34% of the escalation contract value, which is Rp. 53,048.010,455. The escalation percentage obtained at 1.34% was still able to offset the inflation that occurred at 1.28%.